2005
DOI: 10.1007/s00125-005-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring of blood glucose in type 2 diabetes and long-term outcome: an epidemiological cohort study

Abstract: Aims/hypothesis: The aim of this study was to obtain epidemiological data on self-monitoring of blood glucose (SMBG) in type 2 diabetes and to investigate the relationship of SMBG with disease-related morbidity and mortality. Methods: The German multicentre Retrolective Study 'Self-monitoring of Blood Glucose and Outcome in Patients with Type 2 Diabetes' (ROSSO) followed 3,268 patients from diagnosis of type 2 diabetes between 1995 and 1999 until the end of 2003. Endpoints were diabetesrelated morbidity (non-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
196
2
18

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(221 citation statements)
references
References 36 publications
5
196
2
18
Order By: Relevance
“…As shown in Table 1, studies of BGM in T2DM have presented mixed conclusions. Several have shown a clear benefit from frequent BGM (11,12,(28)(29)(30). This has been particularly evident for patients with T2DM who are receiving insulin therapy, especially involving multiple daily injections (MDI), "basal-bolus" therapy, or insulin pump (continuous subcutaneous insulin infusion) (31).…”
Section: History Of Gm In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, studies of BGM in T2DM have presented mixed conclusions. Several have shown a clear benefit from frequent BGM (11,12,(28)(29)(30). This has been particularly evident for patients with T2DM who are receiving insulin therapy, especially involving multiple daily injections (MDI), "basal-bolus" therapy, or insulin pump (continuous subcutaneous insulin infusion) (31).…”
Section: History Of Gm In Diabetesmentioning
confidence: 99%
“…Both capillary blood glucose monitoring (BGM) and continuous glucose monitoring (CGM) with interstitial fluid sensors enable patients to better understand the impact of diet, exercise, illness, stress, and medications on glucose levels and to recognize and treat hypoglycemic and hyperglycemic episodes. Likewise, both BGM and CGM have been shown to improve the efficacy and safety of diabetes therapy (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…11 It demonstrated that morbidity and mortality were significantly lower in patients doing SMBG (adjusted hazard ratios 0.68 and 0.49 respectively). In other words morbidity and mortality was respectively 32% and 51% lower in patients who do SMBG.…”
Section: Cpd Articlementioning
confidence: 96%
“…The emergence of test strips and glucometers in the last 30 years has enabled the glucose concentration self-monitoring and this has gradually replaced the relatively inaccurate and inconvenient measurement of glucose in urine [3][4][5][6][7][8][9][10][11][12][13] . A large amount of attention is given to the frequency of self-monitoring and its effectiveness [14][15][16] . In 1993, the well known study DCCT (Diabetes Control and Complications Trial) emphasized that in PWD1 SMPG should be performed at least four times daily and subsequently corrected with intensive insulin therapy 17,18 .…”
Section: Introductionmentioning
confidence: 99%